Factor Affecting Work Moral of Academic and Planning Bureau Officer, Agricultural Land Reform Office - Sripamorn , Thitipan; Noppanatwongsakorn, Rachen (Dhammathas Academic Journal, 2020)
This research is intended to study: 1) factors affecting the work morale of Academic and Planning Bureau officer, Agricultural Land Reform Office, 2) the recommendation for the improvement of work morale condition in Academic and Planning Bureau officer, Agricultural Land Reform Office. Data were collected from a population of 64 people by using Questionnaire. The population was the Academic and Planning Bureau officers. The statistics tools for data analysis were Mean, Average, Standard deviation, and One way Anova analysis. The research found that: 1. The level of opinion toward the factors affecting the work morale were at the high level (µ = 4.16). This result demonstrated that the highest opinion level is the justice in department (µ = 4.46), Second rank are the relationship between supervisors and subordinates (µ = 4.35), the sufficiency of income (µ = 4.18), the welfare of department (µ = 4.18), the working (µ = 4.16), and the opportunity to advance in the position respectively (µ = 4.16). 2. The study of comparison between the differences of personal data variables with factor affecting the work morale demonstrated that the difference level of work position, job duration has significantly affected the work moral as a significance level 0.05. 3. The results from this research provided the guidelines for improving the work morale were 5 guidelines as follows: 1) The working condition should have a safety insurance system in the working place such as government conveyance or equipment in a safety condition and the quality standard should always be checked 2) The career path promotion should be equal for each job specification 3) The level of income and the department welfare should be ensure the equality in compensation for work from different positions 4) The organization justice and welfare should promote using the moral system in administration 5) The relationship between supervisors and subordinates, the supervisors should be the good role models for subordinates in the department.